2012
DOI: 10.1124/dmd.112.044842
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of a Quantitative Structure Pharmacokinetic Model for Biliary Excretion in Rats

Abstract: poor predictions for our datasets may be due, in part, to the quality and diversity of the data used to derive and test the model. Our reevaluation suggests that hepatobiliary excretion is a process that cannot truly be captured by simple physicochemical descriptors when examining chemically dissimilar compounds. A simple approach involving a limited number of physicochemical predictors may be useful when examining a structurally similar series of compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…In other words, although according to fU, acidity and basicity (dissociation in general) increase the biliary excretion of compounds, this is true only for large dissociated molecules. The positive effect of polarity and dissociation on biliary excretion is in agreement with the literature, where for example polar surface area (18) and an acidity indicator (17,23) have been included in linear QSAR models. Also according to this equation, compounds containing many methyl groups (SsCH3) and those that are highly branched containing >CH− groups (SsssCH) have lower biliary excretion.…”
Section: Regression Modelssupporting
confidence: 89%
See 2 more Smart Citations
“…In other words, although according to fU, acidity and basicity (dissociation in general) increase the biliary excretion of compounds, this is true only for large dissociated molecules. The positive effect of polarity and dissociation on biliary excretion is in agreement with the literature, where for example polar surface area (18) and an acidity indicator (17,23) have been included in linear QSAR models. Also according to this equation, compounds containing many methyl groups (SsCH3) and those that are highly branched containing >CH− groups (SsssCH) have lower biliary excretion.…”
Section: Regression Modelssupporting
confidence: 89%
“…They also developed a multiple linear regression model, but in addition to more common molecular descriptors, they employed free energy of aqueous solvation calculated from a self-consistent reaction field method. In analysing this model, Gandhi and Morris (18) found that the model failed to generalise further to the new set of compounds and specifically free energy of aqueous solvation was not statistically significant. They argued that a complex process such as hepatobiliary excretion cannot be captured by simple physicochemical properties when examining chemically dissimilar compounds.…”
Section: Comparison Of the Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that the development of a reliable structure-activity model for the prediction of cholephilic compounds is not an easy task (Gandhi and Morris, 2012;Hosey et al, 2014). One explanation for the complexity of structure-activity rationalisation and quantitative prediction of biliary excretion may be the different structural requirements for different transport proteins that are involved in the biliary excretion.…”
Section: Introductionmentioning
confidence: 99%